Religion and the American constitutional experiment - Witte, John, Jr., 1959-; Nichols, Joel A., 1972- (Oxford University Press, 2016)
"This accessible introduction tells the American story of religious liberty from its colonial beginnings to the latest Supreme Court cases. The authors provide extensive analysis of the formation of the First Amendment religion clauses and the plausible original intent or understanding of the founders. They describe the enduring principles of American religious freedom--liberty of conscience, free exercise of religion, religious equality, religious pluralism, separation of church and state, and no establishment of religion--as those principles were developed by the founders and applied by the Supreme Court. Successive chapters analyze the two hundred plus Supreme Court cases on religious freedom--on the free exercise of religion, the roles of government and religion in education, the place of religion in public life, and the interaction of religious organizations and the state. A final chapter shows how favorably American religious freedom compares with international human rights norms and European Court of Human Rights case law. Lucid, comprehensive, multidisciplinary, and balanced, this volume is an ideal classroom text and armchair paperback. Detailed appendices offer drafts of each of the religion clauses debated in 1788 and 1789, a table of all state constitutional laws on religious freedom, and a summary of every Supreme Court case on religious liberty from 1815 to 2015. Throughout the volume, the authors address frankly and fully the hot button issues of our day: religious freedom versus sexual liberty, freedom of conscience and its limitations, religious group rights and the worries about abuse, faith-based legal systems and their place in liberal democracies, and the fresh rise of anti-Semitism, Islamophobia, and anti-Christianity in America and abroad. For this new edition, the authors have updated each chapter in light of new scholarship and new Supreme Court case law (through the 2015 term) and have added an appendix mapping some of the cutting edge issues of religious liberty and church-state relations"--